Church and Psychotherapeutic Approaches in the Treatment of Addicts - Ivanov, Krasimir (Forum Theologicum Sardicense, 2025)
Krasimir Ivanov, Church and Psychotherapeutic Approaches in the Treatment of Addicts. The current paper highlights the importance of a holistic approach to treating individuals suffering from addiction. Cooperation among various professionals—such as doctors, psychologists, psychotherapists, social workers, priests, and others—is crucial. Addiction impacts multiple areas of a person’s life, necessitating a collaborative effort among specialists to address the individual’s needs comprehensively.